Gemensam kodbas i C för mobila plattformar - Svensson, Olle; Törnquist, Robin (My University, 2014)
Development of smartphone applications involves different programming languages for different platforms. Because of this, there is an interest in solutions where code written in one language is used on multiple platforms. This report examines the possibility of a mutual core of code in the programming language C as a solution to the problem. The purpose of the examination has been to determine suitable functionality for the mutual core. The basis for the examination has been three different areas of functionality. Problems identified during the examination in combination with the purpose of the mutual core were used to develop guidelines for suitable functionality. If the purpose of the mutual core is to reduce the time of development, a mutual core was considered as not suitable. Otherwise, a mutual core was considered as suitable if standard functions offered by the C language were used exclusively.
Keywords: Data- och informationsvetenskap; Computer and Information Science